False Discoveries and Luck in the Brazilian Equity Fund Market - Costa, Henrique Lamounier (2021)
In this study I investigate the performance of equity funds in Brazil between January 2001 and January 2021. I do that by applying the False Discovery Rate methodology to the entire sample, as well as to sub-samples separated according to fund administrators being affiliated to commercial banks. I find evidence that some managers are able to generate positive alphas after accounting for luck and that bank-affiliated funds achieve positive (negative) alphas less (more) frequently. The results also show that the location of alphas in the cross-sectional distribution differs according to the sub-samples, which has important academic and practical implications. Lastly, I find evidence of persistence of positive and negative performance when analyzing the entire equity fund sample, but document that non bank-affiliated funds are the responsible for that.